Ancient landslide-dam events in the Jishi Gorge, upper Yellow River valley, China. Issue 3 (May 2014) - Dong, Guanghui; Zhang, Fanyu; Ma, Minmin; Fan, Yuxin; Zhang, Jiawu; Wang, Zongli; Chen, Fahu
Abstract: Some scholars have argued that the formation and outburst of an ancient dammed lake in the Jishi Gorge at ca. 3700 cal yr BP resulted in the destruction of Lajia, the site of a famous prehistoric disaster in the Guanting Basin, upper Yellow River valley, China. However, the cause of the dammed lake and the exact age of the dam breaching are still debated. We investigated ancient landslides and evidence for the dammed lake in the Jishi Gorge, including dating of soil from the shear zone of an ancient landslide, sediments of the ancient dammed lake, and loess above lacustrine sediments using radiocarbon and optically stimulated luminescence (OSL) dating methods. Six radiocarbon dates and two OSL dates suggested that the ancient landslides and dammed lake events in the Jishi Gorge probably occurred around 8100 cal yr BP, and the ancient dammed lake was breached between 6780 cal yr BP and 5750 cal yr BP. Hence, the outburst of the ancient dammed lake in the Jishi Gorge was unrelated to the ruin of the Lajia site, but likely resulted in flood disasters in the Guanting Basin around 6500 cal yr BP.